Soroterapia no pós-operatório de colecistectomias videolaparoscópicas: prática essencial ou dispensável? - Jessimara Ribeiro Henrique (2017)
Perioperative intravenous fluid (IV) administration has been the standard procedure since 1832 and, is a widely used practice sometimes under inadequate criteria. The present work aims at verifying the clinical need that justifies the common IV fluid prescription on the postoperative (PO) period in patients undergoing videolaparoscopic cholecystectomy (CVL) elective. Patients over eighteen years old diagnosed with cholelithiasis, were included in the study and assessed before the operation, in the immediate PO and moments before hospital discharge (1st day postoperative). At the end of the operation, the patients were randomly distributed into the groups: a control group (received PO IV fluids, n = 50) and a study group (no PO IV fluids, n = 50). The amounts of IV fluids infused in the perioperative were quantified, the electric Bioeletrical impedance was carried out, body weight was measured, urinary output was quantified in the PO, plasma creatinine was assessed preoperatively and PO. Postoperative hunger and thirst wellbeing levels were also evaluated, as well as the incidence of nausea and vomiting. Preoperative fasting time, the duration of the operation, postoperative fasting time and the total fasting time were similar between the groups (p > 0,05). Total peroperative IV fluids did not differ between the groups (1500 mL; p > 0,05). The total volume in the perioperative was higher in the control group (3000 vs. 1600 mL; p < 0,05). The urinary volume (0,7 ± 0,3 mL/kg/h vs. 0,8 ± 0,5 mL/kg/h) and preoperative creatinine levels (0,78 ± 0,17 mg/dL e 0,79 ± 0,16 mg/dL) did no differ (p > 0,05), while in the PO, the plasma creatinine levels proved to be higher in the control group (0,62 ± 0,17 mg/dL and 0,54 ± 0,17 mg/dL; p < 0,05). In both groups there was a decrease in postoperative creatinine levels (p < 0,05). Concerning weight variation (preoperative weight postoperative weight), the values were higher in the control group (1,11 ± 0,95 kg vs. 0,84 ± 0,58 kg; p < 0,05). The body water ratio did not differ between measurements, as well as the extracellular water (p > 0,05). The levels of hunger, thirst and wellbeing were similar between the groups (p > 0,05), as well as the incidence of nausea and vomiting. So we conclude that there is no clinical indication that justifies the administration of postoperative IV fluids in patients undergoing laparoscopic cholecystectomy.